Prophylaxis with anti‐inhibitor coagulant complex improves health‐related quality of life in haemophilia patients with inhibitors: results from FEIBA NF Prophylaxis Study. (3rd March 2014) - Stasyshyn, O.; Antunes, S.; Mamonov, V.; Ye, X.; Epstein, J.; Xiong, Y.; Tangada, S.
Summary: The Pro‐FEIBA study reported health‐related quality of life (HRQoL) improved following 6‐month of Factor Eight Inhibitor Bypassing Activity (FEIBA) prophylaxis. This study investigates whether 12‐month of FEIBA prophylaxis improved HRQoL in haemophilia patients with inhibitors. Thirty‐six subjects in a 1‐year prospective, randomized, open‐label, parallel‐design study were randomized to prophylaxis (85 ± 15 U kg −1 every other day) or on‐demand treatment. HRQoL was assessed at screening, 6 and 12‐month termination using the EQ‐5D, Haem‐A‐QoL, Haemo‐QoL and a general pain visual analog scale (VAS). To evaluate changes, paired t ‐tests and criteria for minimally important differences were applied. Repeated measures regression tested the association between annualized bleeding rate (ABR) and physical HRQoL. At 6 and 12 months, prophylaxis subjects reported clinically meaningful improvement in EQ‐5D index (mean improvement, 0.10 and 0.08, respectively) and both clinically meaningful and statistically significant improvements in EQ‐VAS scores (16.9 and 15.7, respectively; P < 0.05) vs. baseline. General pain was significantly reduced during prophylaxis at each follow‐up (mean improvement, 20.3 and 23.2, respectively; both P <0.05). At 12 months, prophylaxis subjects achieved significant improvements in Haem‐A‐QoL Total Score and in four domains: Physical Health, Feeling, View, and Work and School (all P < 0.05). No statistically significant changes, except for Haem‐A‐QoL Physical Health at 6 months, were observed with on‐demand treatment. ABR was decreased by 72.5% with prophylaxis vs. on‐demand treatment ( P = 0.0003) and reduced ABR was associated with better physical HRQoL ( P < 0.05). FEIBA prophylaxis significantly reduced ABR and improved HRQoL in inhibitor patients. Subjects with lower ABR reported better physical HRQoL.